Synthesis of Bis (n-salicylidene-n-phenyl aminato) Palladium (II) complex to prepare a number of biphenyl compounds - Hashem, Md A; Tuli, SK; Mahmud, TB (Bangladesh Journal of Scientific and Industrial Research, 2019)
The non-toxic, stable, Schiff base complex of Na2PdCl4 and N-salicylidene-N-phenyl amine in methanol catalyze the Suzuki-Miyaura coupling reaction to synthesize coupling products (Scheme-1) in good to excellent yields with high purity under mild conditions. Bangladesh J. Sci. Ind. Res.54(3), 223-230, 2019